Transition from identity to bioactivity‐guided proteomics for biomarker discovery with focus on the PF2D platform. Issue 1 (16th September 2015) - Ménoret, Antoine; Crocker, Stephen J.; Rodriguez, Annabelle; Rathinam, Vijay A.; Clark, Robert B.; Vella, Anthony T.
Abstract : Proteomic strategies provide a valuable tool kit to identify proteins involved in diseases. With recent progress in MS technology, high throughput proteomics has accelerated protein identification for potential biomarkers. Numerous biomarker candidates have been identified in several diseases, and many are common among pathologies. An overall strategy that could complement and strengthen the search for biomarkers is combining protein identity with biological outcomes. This review describes an emerging framework of bridging bioactivity to protein identity, exploring the possibility that some biomarkers will have a mechanistic role in the disease process. A review of pulmonary, cardiovascular, and CNS biomarkers will be discussed to demonstrate the utility of combining bioactivity with identification as a means to not only find meaningful biomarkers, but also to uncover functional mediators of disease.